Fabrication, Characterization, and Impact of Heat Treatment on Sliding Wear Behaviour of Aluminium Metal Matrix Composites Reinforced with B4C - Krishna Mohan Singh; Akhilesh Kumar Chauhan (Advances in Materials Science and Engineering)
The aim of this research paper is to find the wear behaviour of Al7075 MMCs. In this investigation, the wear tests on the as-cast and age-hardened specimens were performed on an advanced rotary tribometer. The materials selected for the analysis are Al7075 as a matrix, and the reinforcements are boron carbide. By using stir casting, metal matrix composites are manufactured by adding B4C as a reinforcement particulate in Al7075. The fabricated composites were characterized and the wear behaviour of these composites was carried out on an advanced rotary tribometer. The wt. % of the reinforcements was taken as 6%, 8%, 10%, and 12%. The almost homogeneous blending of reinforcements is shown by the microstructural characterization of Al7075 MMCs. It is observed that due to the rise in weight percentage of the reinforcement to 12% higher hardness is obtained. For 12% of reinforcements, there is an increase in hardness due to the heat treatment than that of the as-cast composites. From this study, it was found that the wear rate is the function of the applied load, microstructure, and volume fraction of the reinforcements. The wear rate was increasing with the sliding velocity.